A bone fragment - Dyantyi, Mbongisi Orlean (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
This novella presents three characters, each occupying a different sphere of reality. One is a 'living dead' who is forced to return to the land of the living for his continued existence. The other is a young woman who, having lost the will to live, must find a purpose if she is to continue living. The third is a young man who dwells more in the inner than the external world. Their lives intersect through the scripture known as 'a fragment of a bone.'
Keywords: South African fiction (English) -- 21st century; Creative writing (Higher education); English language -- Writing; South African fiction (English) -- Study and teaching (Higher)